Evaluation of the properties of natural rubber bio composite and guava residue (Psidium guajava L.) as sustainable application - Hiranobe, Carlos T. [UNESP]; da Silva, Alex R. [UNESP]; Cruz, Marco A.G. [UNESP]; Canhada, João C.S. [UNESP]; Araújo, Samara S. [UNESP]; Rocha, José A. [UNESP]; dos Santos, Harison F. [UNESP]; Ribeiro, Gabriel D. [UNESP]; Tolosa, Gabrieli R. [UNESP]; Santos, Gleyson T.A. [UNESP]; Budemberg, Eduardo R. [UNESP]; de Azevedo, Cláudia G. [UNESP]; et al. (FapUNIFESP (SciELO), 2023)
In juice and pulp extraction, about 10% of fruit waste is generated, which often ends up in landfills that can cause environmental damage, serve as food for insects and rodents, and cause health problems for humans. In this work, micronized guava waste was used as a filler in vulcanized compounds in natural rubber. Mechanical properties such as hardness, tensile strength, tear resistance, and abrasion resistance were evaluated, as well as thermal properties such as thermogravimetric analysis, in addition to scanning electron microscopy, X-ray fluorescence, elemental analysis, and infrared spectroscopy. According to the results of the mechanical properties tests, the addition of up to 20 phr of the filler tends to improve the tensile strength of the composites, resulting in an increase in the density of crosslinks obtained through the Flory-Rehner method. The thermal behavior analyzed by TGA and FTIR spectra were not affected by the incorporation of fillers.
Keywords: bio composite; guava; lignocellulosic biomass; Natural rubber; sustainability